Phenotypic characterization of Boer and Jamunapari goat under farming condition in Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
The objective of the study was to characterize of Boer goats and the Jamunapari goat available in Bangladesh under on-station condition. The study was conducted at Goat and Sheep Research farm of BLRI, Savar, Dhaka from January 2014 to June 2015 and animals were reared under standard intensive management system. The collected data was analyzed by SPSS 17.0 Statistical computer programme. The body coat color of Boer goat was white with reddish-brown head, ears and neck and the body coat color of Jamunapari goats was variety of colors. Both of them had horns but polled Jamunapari goats were also found. The body weight significantly (p